Agency and behavior change in agricultural research for development: New directions for guiding agri-food system transformations - Freed, Sarah; Voss, Rachel C.; Falk, Thomas; Rietveld, Anne M.; Alary, Véronique; Chimonyo, Vimbayi G.P.; Frija, Aymen; Guettou-Djurfeldt, Nadia; Lestrelin, Guillaume; Singh, Sonali; Ndiwa, Aurillia Manjella; Zingwena, Taurai (Elsevier, 2025)
CONTEXT Agri-food system transformations require change across sectors and actors within the system. Initiatives contributing to these changes need to connect system change processes to individual and collective agency and behaviors.